2016
DOI: 10.1371/journal.pone.0167668
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Shear-Wave Elastography Assessments of Quadriceps Stiffness Changes prior to, during and after Prolonged Exercise: A Longitudinal Study during an Extreme Mountain Ultra-Marathon

Abstract: In Table 1, the Sex (male/female) values under Finish and Recovery are incorrect. The values should be 27/0 and 27/0, respectively. Please see the corrected Table 1 here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…To avoid anisotropy of the under-probe tissue, (a) the examination probe was held perpendicular to the tissue and (b) the B-mode image showed continuous striations (muscle fascicle) extending from superficial to deep aponeurosis [ 28 ]. Four permanent waterproof skin landmarks were drawn with a marker under 2D-mode monitoring during the pre-session to keep the same probe location during all the measurements [ 7 ]. To assess the stiffness of the rectus femoris and to differentiate between the superficial and deep muscle regions, two circular ROIs were set inside the muscle belly with the mid-distance of muscle thickness in diameter and without connective tissue inside them ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid anisotropy of the under-probe tissue, (a) the examination probe was held perpendicular to the tissue and (b) the B-mode image showed continuous striations (muscle fascicle) extending from superficial to deep aponeurosis [ 28 ]. Four permanent waterproof skin landmarks were drawn with a marker under 2D-mode monitoring during the pre-session to keep the same probe location during all the measurements [ 7 ]. To assess the stiffness of the rectus femoris and to differentiate between the superficial and deep muscle regions, two circular ROIs were set inside the muscle belly with the mid-distance of muscle thickness in diameter and without connective tissue inside them ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The importance of myotendinous stiffness lies in its influence on the joint stability [ 2 , 3 ] and its relationship to explosive force production [ 4 ] and to stretching–shortening cycle activity performance [ 5 ]. Furthermore, the assessment of small changes in stiffness can be a method of early identification of the development of muscle fatigue, muscle damage or muscle injury [ 6 , 7 ], adaptations to sport practice [ 8 , 9 ] and even age-related changes in myotendinous properties [ 10 ]. The relationship between myotendinous stiffness and sport performance and injury prevention has provoked an increase in the number of studies that aim to describe the stiffness in different conditions [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SWE has been applied to assessing muscle properties in sports‐related injuries and spasticity management, as well as in evaluating common nerve disorders such as carpal tunnel syndrome [7,39].…”
Section: Shear Wave Elastographymentioning
confidence: 99%
“…Moreover, SWE has been used to evaluate quadriceps muscle stiffness changes in competitors during an extreme mountain ultramarathon 330‐km race [39]. The authors found a significant decrease in quadriceps shear modulus upon finishing the race (3.31 ± 0.61 kPa) ( P < .001) compared to baseline (3.56 ± 0.63 kPa), followed by partial recovery after the race (3.45 ± 0.6 kPa) ( P =.002) [39].…”
Section: Shear Wave Elastographymentioning
confidence: 99%
See 1 more Smart Citation